The Communicative Functions of Emojis: Evidence from Jordanian Arabic-Speaking Facebookers - Хаді Хамдан (Психолінгвістика)
Purpose. This paper examines the communicative (also known as pragmatic) functions of the most common five emojis in the Jordanian context as perceived by Jordanian Facebook users.